Ukrainian food journal. Vol. 5. Issue 2 - National University of Food Technologies (My University, 2016)
Міжнародне наукове періодичне видання для публікації результатів досліджень фахівців у галузі харчової науки, техніки та технології, хімії, економіки і управління. International scientific periodical to publish the results of research experts in the field of food science, engineering and technology, chemistry, economics and management.
Keywords: food technologies; biotechnology; microbiology; food chemistry; processes and equipment of food productions; харчові технології; біотехнологія; мікробіологія; харчова хімія; процеси і апарати харчових виробництв; пищевые технологии; биотехнология; микробиология; пищевая химия; процессы и аппараты пищевых производств